Factors Promoting the Use of ICT Hardware in University Libraries in Two Nigerian Regions - Achugbue, Edwin Iroroeavwo; Ahimbisibwe, Kasiisi Benjamin; Odong, Patrick; Azih, Adaeze Chioma (Regional Institute of Information and Knowledge Management, 2023)
Rationale of Study – This paper examined the factors promoting the usage of ICT hardware in university libraries in two Nigerian regions. Methodology – The study adopted a survey type of descriptive research design. The population of the study is 512 librarians from 41 university libraries in two Nigeria regions were used for the study. A questionnaire was used to collect data, and the data were analysed using linear regression. Findings – The study revealed that knowledge, anxiety and librarian attitude are factors promoting the usage of ICT hardware in university libraries in two Nigerian regions. Implications – From the study findings, it was recommended that librarians should be trained on the job to have a robust knowledge of ICT equipment usage to enable them to remain relevant in university libraries. University management and librarians should ensure that working environments are ICT friendly. This will reduce anxiety among librarians expected to render library services through ICT hardware. Finally, librarians should be encouraged to approach ICT facilities in university libraries positively. Originality – The study has provided information on the factors that will influence or promote the use of ICT hardware in university libraries in two Nigerian regions